Effect of roasting as a premilling treatment on the functional and bread baking properties of whole yellow pea flour. Issue 2 (7th November 2019) - Young, Gina; Bourré, Lindsay; Frohlich, Peter; Borsuk, Yulia; Sarkar, Ashok; Sopiwnyk, Elaine; Jones, Stuart; Dyck, Adam; Malcolmson, Linda
Abstract: Background and objectives: There is a growing global interest in partially replacing wheat flour with pulse flours in foods, including bread. However, undesirable flavors associated with pulse flours, especially yellow pea flour, have limited their use in foods. Pretreating pulses prior to milling offers a possible solution for improving the flavor of pulse flours. The objective of this research was to examine the effect of oven roasting and Revtech roasting (with and without steam) on the compositional, functional, and bread baking properties of whole yellow peas. Findings: Regardless of the roasting method used, a roasting temperature of 120°C resulted in flours that retained good functionality and bread baking properties with less detrimental changes in flour color. Bread made with peas roasted at 120°C also had reduced aroma and flavor properties compared to bread made with untreated peas. Conclusions: The strong aroma and flavor properties of yellow peas can be reduced by pretreating the peas prior to milling using conventional oven roasting and Revtech roasting. By selecting the appropriate roasting temperature, flour functionality for bread baking can be maintained. Significance and novelty: Roasting is a useful premilling treatment for yellow peas. Reducing the off‐flavors associated with pulses while maintaining flour functionality will allow for greater use of pulse flours in formulating foods.